2016
DOI: 10.1002/jcp.25423
|View full text |Cite
|
Sign up to set email alerts
|

Chrysophanol Induces Apoptosis of Choriocarcinoma Through Regulation of ROS and the AKT and ERK1/2 Pathways

Abstract: Chrysophanol is an anthraquinone compound, mainly isolated from rhubarb, with anti-cancer effects on some types of cancer cells. However, effects of chrysophanol on human choriocarcinoma cells are not known. Therefore, the objective of this study was to determine effects of chrysophanol on choriocarcinoma cells (JAR and JEG-3) and identify signal transduction cascades activated by chrysophanol. Results of present study, showed that chrysophanol decreased cell viability and induced apoptosis of JEG-3, but not J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 33 publications
7
68
0
Order By: Relevance
“…These observations are also supported by previous studies where chrysophanol has been shown to trigger apoptosis of the breast cancer cells [16]. Chrysophanol has been shown to induce anticancer effects through the activation of the ROS machinery [12,13] and in this study, we found that chrysophanol increased the ROS levels and at the same time decreased the MMP levels. Mitogen-activated protein kinase signaling pathway is often activated in the cancer cells [17] and in this study, we found that chrysophanol could block this pathway in the CH157-MN cells suggestive of the potent anticancer effects…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These observations are also supported by previous studies where chrysophanol has been shown to trigger apoptosis of the breast cancer cells [16]. Chrysophanol has been shown to induce anticancer effects through the activation of the ROS machinery [12,13] and in this study, we found that chrysophanol increased the ROS levels and at the same time decreased the MMP levels. Mitogen-activated protein kinase signaling pathway is often activated in the cancer cells [17] and in this study, we found that chrysophanol could block this pathway in the CH157-MN cells suggestive of the potent anticancer effects…”
Section: Discussionsupporting
confidence: 81%
“…In yet another study, chrysophanol halted the ATP synthesis in liver cancer cells [12]. In choriocarcinoma cells, chrysophanol causes apoptosis via modulation of ROS [13]. These studies suggest that chrysophanol may prove a potent anticancerous molecule.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[17][18][19] However, the mechanism of action of chrysophanol has not been elucidated for ovarian cancer. Previous studies demonstrated that chrysophanol triggers cell death in several cancer cell lines, including liver cancer, lung cancer, prostate cancer, and gestational choriocarcinoma, through the induction of mitochondrial dysfunction and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…13. 198,199 Reduced graphene oxide (RGO) sheets are prepared by heating GO sheets aer assembly. The modied Ti surfaces were then tested using a reciprocating pin on plate tribometer under dry conditions against a silicon nitride ball under 100 mN load and 1 Hz frequency.…”
Section: 196mentioning
confidence: 99%